Immune microenvironment dynamics in breast cancer during pregnancy: impact of gestational age on tumor-infiltrating lymphocytes and prognosis - Sajjadi, Elham; Venetis, Konstantinos; Ivanova, Mariia; Noale, Marianna; Blundo, Concetta; Di Loreto, Eugenia; Scarfone, Giovanna; Ferrero, Stefano; Maggi, Stefania; Veronesi, Paolo; Galimberti, Viviana E.; Viale, Giuseppe; et al. (Frontiers in Oncology, 2023)
Background: Breast cancer during pregnancy (PrBC) is a rare condition known for its aggressive clinical behavior and tumor-infiltrating lymphocytes (TILs) play a significant role in prognosis. However, little is known about the dynamics of the immune landscape in PrBC based on gestational age. This study aimed to investigate the relationship between gestational age at breast cancer diagnosis and the composition of the tumor microenvironment (TME). Methods: A total of 108 PrBC were selected from our Institutional registry and categorized by pregnancy trimester. For all cases, TILs were profiled according to the International TILs Working Group recommendations, and subtyped by CD4, CD8, and FOXP3 immunohistochemistry. PD-L1 was tested according to the combined positive score (CPS) using the IHC 22C3 pharmDx assay. The statistical approach encompassed Fisher's and Chi-squared tests, with appropriate adjustments for multiple comparisons, logistic regression models, and Kaplan-Meier survival analyses. Results: The proportion of patients with poorly differentiated (G3) neoplasms increased as the gestational age advanced. (1st, n=25, 56.8%; 2nd, n=27, 69.2%; 3rd trimester, n=21, 87.5%; p=0.03). The histologic subtypes as well as the hormone receptor (HR) and HER2 status did not show significant changes across different pregnancy trimesters. In HR+/HER2– subtype, there was a higher proportion of tumors with high/moderate TILs in the early phases of pregnancy, similar to FOXP3 expression (TILs: 1st, n=10, 35.7%; 2nd, n=2, 10.5%; 3rd trimester, n=0; p=0.02; FOXP3: 1st, n=10, 40%; 2nd, n=3, 15.8%; 3rd trimester, n =0; p=0.03). The median follow-up for our cohort was 81 months. Patients who relapsed after a breast cancer diagnosis during the 1st trimester were more frequently PD-L1-negative, unlike those with no disease recurrence (n=9, 100% vs. n=9, 56.3%; p=0.03; hormone therapy and n=9, 100% vs. n=7, 53.9%; p=0.02; chemotherapy). No statistically significant differences were seen among the three trimesters in terms of survival outcome. Conclusion: The TME dynamics of HR+/HER2- PrBC vary based on gestational age, suggesting that immune tolerance events may occur in PrBC at earlier stages of pregnancy. The observed decrease in TILs and FOXP3 expression during later gestational age could explain the increased aggressiveness of tumors diagnosed at that stage.